Localism and the ancient Greek city-state - Beck, Hans, 1969- (Chicago ; London)
xiii, 267 sayfa
Keywords: “This is a fluently written history of ancient Greece seen from the perspective of localism and the origins of the Greek City-State. Much like our own time, from the 8th century BCE until and even beyond its imperial end, the Greek world was constantly expanding and experiencing growing connectivity with the world at large. Conquest, exploration and exchange all grew Greece's global presence and helped develop an expanded world where a need to define and cherish the local would inevitably arise. Beck draws on a breathtaking range of materials: texts, some of them rare, by both well-known and obscure writers; numismatics, visual culture, pottery analysis, landscape and traditional field archaeology. He brings all this together in developing fine-grained case studies about tensions between metropolis and local communities such as Miletus, Ithaca, and rural Attica in relation to Athens and other major centers“ --